We are "Negative" But We are Not Healed: The Cultural Construction of Leprosy and Gender in Bangladesh - E. Wilson-Moore, Margot (Culture, 1995)
In this paper I discuss the ways in which leprosy is culturally constructed in Bangladesh and the ways in which that construction impacts patient experiences of leprosy. Concepts of pollution and purity are strong and leprosy patients are routinely ostracized by their families and communities. As a result patients are reluctant to label themselves and often postpone diagnosis for fear of the social repercussions. Nevertheless, male patients tend to seek treatment earlier in the course of the disease than females do. Women regularly wait until they are severely disabled before seeking treatment. Women in Bangladesh are routinely viewed as improductive, non-contributing members of the community. Expected to live virtuous, submissive, secluded lives, their behaviour a symbol for family honour and prestige, women with leprosy are often considered as having failed to meet these criteria and, accordingly, are abandoned by their families without recourse and without support. The seclusion of women provides the opportunity and fear the motive for women to hide their disease for the longest possible time. Understanding these behaviours as logical outcomes of the culturally constructed experience of leprosy provides a focus for developing more inclusive treatment and rehabilitation programming and for addressing not only the physical but the social problems associated with leprosy as well.